Workshop Pengembangan Desain Motif Batik Tanjung dengan Menggunakan Aplikasi Digital - Kuswanto ,; Sofia Tri Septiawati; Ety Yaohanita; Imam Syafi’i; Nur Fitria Wiji Astutik (Abhakte Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the local cultural wisdoms in Tanjung Village is Tanjung Batik, which is not known exactly when Tanjung batik began to exist, but this batik culture has been around for many years. Tanjung Batik has distinctive motifs and color combinations. This batik design development training not only equips individuals with community knowledge and skills but can also develop more varied batik motif designs quickly and without taking a long time using the D-Batik Application. The aim of this community service activity is to provide guidance to the youth/community of Tanjung Village, so that later they can have distinctive batik that shows the identity of Tanjung Village so that it can be patented and can become an item of high selling value and can improve the economic quality of the community in Tanjung Village, Lamongan Regency. . From the results of implementing Community Service, the training participants responded positively and looked satisfied. You can also see the participants' enthusiasm for developing Tanjung batik designs as shown by their active participation in the training. Participants have also demonstrated their understanding of batik design development using the D-Batik application which is supported by their success in practicing independently the process of making batik motif designs using digital applications.